Reactivity of lymphocytes from patients with syphilis towards T. pallidum antigen in the leucocyte migration and lymphocyte transformation tests. Issue 4 (August 1976) - From, E; Thestrup-Pedersen, K; Thulin, H
Abstract : The reactivity of lymphocytes to Treponema pallidum antigen was studied before and after treatment in nine patients with early syphilis using a leucocyte migration test and a lymphocyte transformation test. Lymphocyte reactivity was also investigated in six patients treated for syphilis within the last 4 years, and in five untreated patients with a positive result to the T. pallidum immobilization test, but negative results to other serum tests for syphilis antibodies and without any known exposure to risk of infection by syphilis. Ten seronegative patients with different dermatological disorders served as a control group. A significant increase in lymphocyte reactivity to T. pallidum antigen was recorded in both tests in vitro after treatment. There was no difference in lymphocyte reactivity to T. pallidum antigen between the other patients studied and the control group. In early syphilis the spontaneous migration was found to be inhibited before treatment. Tuberculin skin tests were also performed and found to be suppressed in patients with primary and secondary syphilis. No difference in phytohaemagglutinin response was found between any of the groups. Plasma from patients with primary and secondary syphilis was found to change the in vitro reactivity of normal lymphocytes when stimulated with different mitogens.